PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS ASURANSI UNIT LINK DI PT. ASURANSI JIWA MANULIFE INDONESIA, JAKARTA - Nanda Mutia Apsari, Budiharto, Rinitami Njatrijani (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
To increase public interest in the insured, the insurance company issuing insurance products by combining the functions of protection and unit-linked investment called. Society is quite enthusiastic about this product, because the development of investment in Indonesia is quite rapid in the past decade. It makes opportunities for the insurance industry in Indonesia is growing more slowly than other countries. The growth of unit-linked proceeded to make even the life insurance industry today are more focused on selling products. This study aimed to determine whether the implementation of unit-linked insurance in PT. Asuransi Jiwa Manulife Indonesia in accordance with the existing arrangement is the Chairman of Bapepam and financial institutions Kep-104/BL/2006 on Unit Linked Products and Government Regulation Number 73 Year 1992 concerning Insurance Business, as well as to know what the legal protection provided by PT . PT. Asuransi Jiwa Manulife Indonesia appears logical for the clients in case of problems in the agreement. This study uses empirical juridical approach, which is done by examining the norm das solen and real implementation specifications descriptive-analytical study which attempted to portray the legislation in force associated with the theories of law and positive law enforcement practices. The results showed that the implementation of unit-linked insurance in PT. Asuransi Jiwa Manulife Indonesia has fulfilled a variety of settings in the Chairman of Bapepam and financial institutions Kep-104/BL/2006 on Unit Linked Products and Government Regulation Number 73 Year 1992 concerning Insurance Business, although there is no specific regulation on the implementation of unit-linked insurance itself. Forms of legal protection for the insured in the soul assuransi link unit on PT. Asuransi Jiwa Manulife Indonesia, Jakarta is through the application of provisions of Law. 8 of 1999 on Consumer Protection. With regard to corporate responsibility issuing unit-linked life insurance to customers as contained in Article 26 of BFL, a company that markets life insurance unit-linked insurance is responsible to the customer or the insured to meet any guarantee of protection expressly stated in the policy. Based on the results of this study suggested to the Government authorities should conduct more rigorous oversight of the products are unit-linked life insurance marketed in Indonesia to comply with regulations. Supervision may be accompanied by sanctions against the insurance company itself. In terms of legal protection, the government should supervise the performance of insurance agents more closely, whether insurance agencies owned by the insurance company already has a license from the Insurance Council of Indonesia (DAI) or not, because the problem-an issue may arise because agents unprofessional.